Positioning at the Olympic Winter Games: Examining the targeting of Olympic Winter Sports by medal-winning nations - Weber, A. C.; De Bosscher, V.; Kempf, H. (Sport, Business and Management, 2019)
Purpose: Since the 1990s, the International Olympic Committee has offered nations more medal-winning opportunities at every Winter Games. Meanwhile, many countries are constrained by their limited financial resources to target sports strategically. The purpose of this paper is to examine the targeting approaches to Olympic Winter Sports of National Sports Agencies (NSAs), and to identify the factors they assess in the decision-making process. Design/methodology/approach: The data were collected through semi-structured interviews with 11 decision makers of medal-winning NSAs at the 2014 Sochi Games. The data were then analysed with reference to strategic management in an approach which combines a resource-based view (RBV) with a market-based view (MBV) to build a competitive advantage. Findings: The results show that NSAs, like firms, combine an internal analysis that reflects the RBV on resources and capabilities (e.g. athletes` performance per sport and sport-specific elite sport system), with an external analysis of the competitive environment that reflects an MBV (e.g. sport`s medal market size and intensity of competition at Games) to target sports. Using this information, two phases were distinguished: first, the target sports are identified and finance is prioritised accordingly; second, the allocation of the nation`s resources is constantly reviewed in order to optimise it. Research limitations/implications: Even though social desirability bias in the responses could not be fully excluded, the findings can help policy-makers to distinguish between the internal and external factors identified in this study, and to make more strategic decisions by combining RBV and MBV approaches to build-up their nation`s competitive advantage. Originality/value